Implementation of An-Nadhofatu Minal Iman in Building Clean and Healthy Living Behavior - Fina Indriyanti Fina Indriyanti; Hasna Ulpa Ujiah Simamora; Kholidah Agustina; Bila Rona Amin; Mina Ainun Harahap; Anil Fadilah Munthe; Fitry Dahnia Hasibuan; Nuri Yanni Siregar; Muhammad Fakih Hasibuan (Journal of Development Research, 2023)
Environmental cleanliness is one of the main factors for a clean, healthy, and comfortable life. Avoid various kinds of diseases that are desired by everyone. In maintaining the cleanliness of the environment, not only ourselves, but also the community, and also the government. The lack of public attention to the environment is very familiar today. Cleanliness is part of faith is a sentence that is not heard in the ears of every human being. The sentence is the meaning of the hadith which reads "An Nadhofatu Minal Iman". In North Padang Lawas Regency, there is an advice or philosophy, namely Poda Na Lima. Poda Na Lima consists of five elements found in the Angkola Batak community or the Mandailing tribe. The results of the study are observations made by Regular Community Service Program students at the State Islamic University of North Sumatra for the period 2021-2022 located in Siringki Jae village, Halongonan District, North Padang Lawas Regency, and there are still many people who do not realize the importance of clean and healthy living behavior and do not keep the environment clean.